Utilization of Generative Artificial Intelligence in the Development of Islamic Religious Education Learning Media - Fakih, Muhammad; Maulana, Gilang; Syifa’unnufus, Syifa’unnufus (Jujurnal Publisher, 2024)
The rapid development of Generative Artificial Intelligence has created new opportunities to develop innovative, adaptive, and interactive learning media in Islamic Religious Education. This study aims to analyze the use of Generative Artificial Intelligence in developing learning media for Islamic Religious Education by examining its opportunities, challenges, conceptual foundations, and implementation strategies. This study uses a qualitative literature review approach based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, with literature collected from leading academic databases and analyzed through thematic analysis and narrative synthesis. The findings indicate that Generative Artificial Intelligence improves the efficiency, creativity, personalization, and interactivity of learning media development when integrated with knowledge of technology, pedagogy, and content. However, its implementation requires teacher professional competence, responsible AI practices, and Islamic ethical principles to ensure the validity and appropriateness of learning content. This study concludes that Generative Artificial Intelligence has significant potential to support the digital transformation of Islamic Religious Education through the development of innovative, effective, and ethically responsible learning media.